2018
DOI: 10.1038/s41467-018-05907-w
|View full text |Cite
|
Sign up to set email alerts
|

Ventral hippocampal OLM cells control type 2 theta oscillations and response to predator odor

Abstract: Dorsal and ventral hippocampus regions exert cognition and emotion-related functions, respectively. Since both regions display rhythmic activity, specific neural oscillatory pacemakers may underlie their functional dichotomy. Type 1 theta oscillations are independent of cholinergic transmission and are observed in the dorsal hippocampus during movement and exploration. In contrast, type 2 theta depends on acetylcholine and appears when animals are exposed to emotionally laden contexts such as a predator presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 61 publications
9
90
0
Order By: Relevance
“…Therefore, one possibility is that the low-theta oscillations we observed are indeed related to the rodent Type 2 theta, but this signal in humans has a broader functional role beyond anxiety, perhaps including episodic memory and other types of cognitive processes that involve the anterior hippocampus (Bannerman et al, 2004; Mitchell et al, 2008). Our interpretation is consistent with the recent finding that slower, Type 2 theta oscillations in rodents can be generated by a distinct network of cells in the ventral hippocampus (Mikulovic et al, 2018), which is homologous to the anterior hippocampus in humans (Colombo et al, 1988; Amaral & Witter, 1989; Moser & Moser, 1998; Strange et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, one possibility is that the low-theta oscillations we observed are indeed related to the rodent Type 2 theta, but this signal in humans has a broader functional role beyond anxiety, perhaps including episodic memory and other types of cognitive processes that involve the anterior hippocampus (Bannerman et al, 2004; Mitchell et al, 2008). Our interpretation is consistent with the recent finding that slower, Type 2 theta oscillations in rodents can be generated by a distinct network of cells in the ventral hippocampus (Mikulovic et al, 2018), which is homologous to the anterior hippocampus in humans (Colombo et al, 1988; Amaral & Witter, 1989; Moser & Moser, 1998; Strange et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…In conclusion, our data reveal the preferential recruitment of IS3 cells specifically during theta oscillations. Thus, a slow inhibition provided by these cells to OLM interneurons via the α5 GABA A receptor-containing synapses [73,74] may be responsible for pacing the OLM activity at theta frequency and generation of theta-oscillations (e.g., type II theta associated with the emotional context and generated in ventral hippocampus) [29].…”
Section: Discussionmentioning
confidence: 99%
“…The OLM cells are known to fire at the trough of theta oscillation, but can be silent during the sharp wave-associated ripples (SWRs) via yet unknown mechanisms [4][5][6][7]19]. By inhibiting distal and disinhibiting proximal dendrites of CA1 PCs, OLM cells have been considered essential for modulating the integration of the temporoammonic (TA) vs Schaffer collaterals (SC) inputs [20][21][22][23], burst firing of PCs [24,25] and generation of theta oscillations in vitro [26][27][28] and in vivo in the ventral hippocampus [29]. Thus, given that synchronous activation of IS3 cells is capable of pacing the OLM interneuron activity at theta frequency [18], the IS3 input to OLM cells may act as a gear mechanism providing for rhythmic gating of the SC vs TA inputs in the CA1 area.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that OLM cells play a gating role ( Leão et al, 2012 ), akin to earlier work by Blasco-Ibáñez and Freund (1995) who showed that “horizontal SOM+ interneurons” (i.e., putative OLM cells) could act as a switch controlling activation of local pyramidal cells via Schaeffer collaterals or perforant path input from entorhinal cortex. Further work has shown that OLM cells in intermediate regions of CA1 exert a bidirectional control on learning and memory ( Siwani et al, 2018 ), and ventral OLM cells control Type 2 theta rhythms and are associated with increased risk-taking ( Mikulovic et al, 2018 ). In a recent modeling study, OLM cells were shown to be critical in producing a robust intrinsic theta output ( Chatzikalymniou and Skinner, 2018 ), which suggests that their neuromodulation may be key to the maintenance of theta rhythms.…”
Section: Discussionmentioning
confidence: 99%